Utilisation of antibody technology to purify CMV-induced plasma membrane proteins - Roig, Pilar Farran (My University, 2015)
Several human cytomegalovirus (HCMV) induced proteins have been found in human embryonic lung fibroblast cells (HEF). Monospecific antibodies against three of the glycoproteins (54Kd, 62Kd and 90Kd) raised in rabbits were used to purify the different glycoproteins from HEF membrane preparations through affinity chromatography columns. The optimal conditions for the membrane preparation and the affinity chromatography columns were determined.